PENGATURAN PAJAK PERTAMBAHAN NILAI ATAS JASA NOTARIS / PEJABAT PEMBUAT AKTA TANAH (PPAT) - Dwi Azhari (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
The thesis title is "The Value Added Tax Regulation On Notary/Official Certifier of Title Deeds (PPAT) Services". The research formulates the problems of why Notary/Official Certifier of Title Deeds Notary (PPAT) have to collect Value Added Tax (PPN) on services, the criterias of Notary / Official Certifier of Title Deeds (PPAT) services which can be charged with Value Added Tax, and The Obstacles of its application and alternatives can be taken to these obstacles.  Based on Law Number 42 Year 2009, the Notary / Official Certifier of Title Deeds (PPAT) is one of the Taxable Person for any services rendered to the public. To examine and answer the problems mentioned above, this thesis uses normative legal study that analyzing law enforcement. Performed by examining the legal materials, such as the study of the principles of law, positive law, the rule of law, and rules of legal norms. The approach method used in this research was Legislation Approach, and Historical Approach.  The result shows that the Notary who have to collect value added tax is the Notary who included in the Entrepreneur category. Main obstacles encountered in the application of Value Added Tax is society refuse to pay value added tax, because they considered they are subject to double taxation, therefore to overcome these, Notary / Official Certifier of Title Deeds (PPAT) charged with  those. It can be done because in the Value Added Tax that is known as tax shifting. It is suggested that the Government should make special regulations in imposing value added tax on legal services provided by a Notary, so the Notary is not classified as an entrepreneur and then kept the image of Notary as an Public Officials. Key words: Value Added Tax of Notary’s services, Taxable entrepreneur, Taxable services and public officials.